High-elasticity anti-aging waste rubber modified asphalt and preparation method thereof
By combining the modified oak bark with waste rubber particles, and through steps such as double-roll grinding and vulcanization, the problem of low cross-linking of traditional waste rubber particles in modified asphalt is solved, significantly improving the anti-aging performance and service life.
Patent Information
- Application Number
- CN202510003360.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-22
AI Technical Summary
Traditional waste rubber particles have low crosslinking in modified asphalt, resulting in poor anti-aging properties, and the addition of cellulose may reduce elasticity and tensile strength.
By mixing the oak bark with n-octadecyl trimethoxysilane, the modified oak bark is generated and combined with waste rubber particles. The cross-linking degree and anti-aging properties of the rubber particles are improved by using steps such as double-roll grinding and vulcanization.
It significantly improves the cross-linking degree of waste rubber particles in asphalt, enhances the structural strength and stability of the material, extends the service life, and improves the anti-aging performance, and can effectively resist environmental stresses such as high temperature, ultraviolet rays and oxidation.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of modified asphalt environmentally friendly materials, and in particular to a high-elasticity anti-aging waste rubber modified asphalt and a preparation method thereof. Background Art
[0002] In the study of rubber particle modified asphalt materials, the elasticity of rubber particles has a certain influence on the cross-linking degree of asphalt. The elasticity of rubber particles mainly comes from the flexibility and mobility of their molecular chains, while the cross-linking degree is the embodiment of the number of cross-linking points between molecular chains. Moderately improving the elasticity of rubber particles can increase the freedom of movement of their molecular chains, which helps to form a more uniform and stable cross-linking structure in the modified asphalt, thereby promoting the cross-linking reaction to a certain extent. Due to long-term service, the elasticity of traditional waste rubber particles has greatly decreased, and the cross-linking degree has been greatly reduced, making it difficult to form a stable cross-linked network structure in asphalt. Poor cross-linking performance makes it difficult for rubber particles to be effectively integrated into the asphalt system, resulting in a decrease in the overall stability and durability of the modified asphalt. In harsh environments such as ultraviolet aging and high-temperature oxidation, this weak cross-linking structure is prone to decomposition and performance degradation, which in turn affects its anti-aging performance and greatly shortens its service life. Therefore, improving the elasticity of waste rubber particles is the key to enhancing the anti-aging performance of its modified asphalt.
[0003] One of the most popular biofillers is cellulose, which is obtained from trees, leaves and grasses. Its fibers can be used as a rubber modifier to improve elasticity and cross-linking. However, adding more than 10 parts of cellulose may reduce elasticity and slightly reduce tensile strength. In the search for new solutions, few researchers have focused on using bark as a rubber modifier. Oak bark, as a natural plant resource, is rich in lignin, cellulose, holocellulose and a variety of extracts. As natural polymers, lignin and cellulose have excellent mechanical properties and reinforcing effects, so they are widely used in material modification. The cellulose in oak bark not only has good energy efficiency characteristics, but also can effectively improve the mechanical properties and durability of composite materials through the particularity of its structure. In addition, phenolic substances in oak bark, such as tannic acid, show significant anti-aging effects due to their strong antioxidant and anti-free radical capabilities. These phenolic compounds can delay aging and enhance anti-ultraviolet and anti-oxidation properties during the use of materials, thereby improving the long-term stability and service life of modified materials. Therefore, oak bark not only has rich resource potential, but its modification effect also provides strong support for improving the performance of a variety of materials, especially in terms of weather resistance and anti-aging, and has broad application prospects.
[0004] Therefore, oak bark can be used to modify waste rubber particles, thereby improving the elasticity of waste rubber particles and the anti-aging properties of their modified asphalt. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a highly elastic and aging-resistant waste rubber modified asphalt and a preparation method thereof, which solves the problems mentioned in the background technology that the degree of cross-linking of waste rubber particles in modified asphalt is poor, resulting in difficulty in forming a stable network structure when compounded with the asphalt matrix, resulting in poor anti-aging performance, and the addition of cellulose may reduce elasticity and slightly reduce tensile strength.
[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing modified waste rubber particles, comprising the following steps:
[0007] S1. preparing a modified mixture: mixing oak bark and n-octadecyltrimethoxysilane in situ to generate modified oak bark, and then adding the oak bark into waste rubber particles to generate a modified mixture;
[0008] S2. Premix preparation: preparing a premix containing a modified mixture, a dispersant and a cross-linking activator by a double-roll mill;
[0009] S3, preparing modified waste rubber particles: the obtained premix is sequentially mixed with an accelerator and sulfur for vulcanization reaction, and then a double-roll mill is used to prepare modified waste rubber particles. The modified waste rubber particles are stored separately in a sealed foil at room temperature.
[0010] Preferably, the ratio of each component, such as the ratio of modified oak bark, waste rubber particles, crosslinking activator and vulcanizing agent, is to achieve the best crosslinking degree and anti-aging performance, ensuring that the final product has excellent mechanical properties and environmental tolerance during use. In terms of weight, the ratio of the waste rubber particles, n-octadecyltrimethoxysilane, oak bark, dispersant, crosslinking activator, accelerator and sulfur is 100:1:5 to 25:2:5:1.5:2.
[0011] Preferably, the density of n-octadecyltrimethoxysilane is 0.88 g / cm 3 ; n-octadecyltrimethoxysilane was selected as a modifier to improve the hydrophobicity of oak bark and its compatibility with the asphalt matrix, ensuring the formation of a stable interfacial bonding force during the mixing process, thereby enhancing the dispersibility and bonding force of waste rubber particles in asphalt.
[0012] Preferably, the waste rubber particles are crushed from automobile tires and contain natural rubber and synthetic rubber.
[0013] Preferably, the crosslinking activator is zinc oxide; peroxide is used as a crosslinking activator to efficiently generate free radicals at an appropriate temperature, promote the crosslinking reaction inside the rubber particles, and then form a denser crosslinking network, thereby enhancing the structural stability and mechanical properties of the particles.
[0014] Preferably, the dispersant is stearic acid with a density of 0.94 g / cm 3 .
[0015] Preferably, during the vulcanization reaction, an appropriate amount of accelerator and sulfur are preferably used to improve the efficiency and crosslinking density of the vulcanization reaction, ensure that the rubber particles form a stable sulfur bridge structure in the asphalt matrix, and enhance the anti-aging performance and long-term durability. The accelerator is 2-mercaptobenzothiazole, with a density of 1.29 g / cm 3 The sulfur density is 1.8 to 2.36 g / cm 3 .
[0016] Preferably, the vulcanization reaction can be carried out in a hydraulic press at high temperature, preferably using a suitable vulcanization temperature and time to ensure the formation of a uniform and highly cross-linked vulcanized rubber structure, thereby improving the anti-aging performance of the waste rubber particles in asphalt. The vulcanization parameters of the vulcanization reaction include a temperature of 160°C, a pressure range of 150 to 180 bar, and a curing duration of 4 minutes.
[0017] Preferably, in step S2 and step S3, in the double-roll grinding stage, a relatively low grinding temperature and an appropriate grinding time are preferably used to avoid degradation of the rubber particles due to overheating, while ensuring that the modified oak bark and the waste rubber particles are fully mixed to achieve the best cross-linking effect. The roller temperature of the double-roll grinder is 30-35° C., and the grinding time is 10 minutes.
[0018] On the other hand, to achieve the above-mentioned purpose, the present invention also provides the following technical solution: a modified waste rubber particle, compared with the unmodified waste rubber particles, the modified waste rubber particles have a tensile strength increased by 38%, an elongation at break increased by 28%, and a 100% elongation stress value decreased by 16%.
[0019] On the other hand, to achieve the above-mentioned purpose, the present invention also provides the following technical solution: application of modified waste rubber particles in asphalt.
[0020] Preferably, the No. 70 base asphalt is heated to 180°C, modified waste rubber particles are added, the shearing time is 4 hours, and the shearing temperature is 200°C; after the shearing is completed, the asphalt is stirred and developed, and 0.08% sulfur stabilizer is added during the stirring and development, the stirring temperature is 190°C, and the stirring time is 2 hours. After stirring and developing, a modified asphalt with enhanced anti-aging properties is obtained.
[0021] Preferably, the added amount of the modified waste rubber particles is 15-25% of the mass of the asphalt.
[0022] Preferably, the softening point of the modified asphalt is 77.5° C., the creep stiffness is 115.2 MPa, and the strength retention rate before and after PAV aging is 0.598.
[0023] The beneficial effects of the present invention are as follows: the present invention significantly improves the crosslinking degree of waste rubber particles in asphalt, thereby enhancing the structural strength and stability of the material and extending the service life; at the same time, through the steps of silane modification, crosslinking activation and vulcanization, the anti-aging performance of the rubber particles is improved, so that it can effectively resist environmental stresses such as high temperature, ultraviolet rays and oxidation, ensuring the performance reliability in long-term use. In addition, the compatibility of the modified waste rubber particles with asphalt is improved, the interfacial bonding force between the two is enhanced, and the mechanical properties of the asphalt, including anti-aging performance, tensile strength, tear strength and elastic modulus, are improved. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] Oak bark can replace synthetic fillers and anti-aging agents in composites, but requires surface modifiers to make it compatible with scrap rubber particles. Incorporating silane into oak bark can achieve better dispersion and smaller oak bark particles in scrap rubber particles.
[0026] Oak bark raw materials are widely available, low in cost and excellent in performance. The present invention provides a method for improving the elastic properties of waste rubber particles and the anti-aging properties of modified asphalt using plant-based materials. In the process of preparing modified waste rubber particles, first, n-octadecyl trimethoxysilane is used to modify the oak bark to make it more stable in long-term use. This modification not only improves the hydrophobicity of the oak bark, but also significantly enhances its compatibility with rubber particles, thereby ensuring the uniform dispersion of the rubber particles in the asphalt matrix. Then, the synergistic effect of the dispersant and the cross-linking activator forms a preliminary cross-linking structure between the modified oak bark and the waste rubber particles during the double-roll grinding process, further enhancing the overall stability of the particles. Subsequently, the accelerator and sulfur added during the vulcanization process will cause the double bonds in the rubber particles to react to form a high-density sulfur bridge cross-linking network. This cross-linking network not only greatly improves the mechanical strength and elasticity of the rubber, but also significantly enhances its anti-aging ability, ensuring that excellent performance is maintained under harsh environments such as high temperature, oxidation and ultraviolet rays. Finally, high-temperature vulcanization in hydraulic presses and metal molds further consolidates the cross-linked structure inside the rubber particles, making them more durable and long-term stable. This series of comprehensive modification and cross-linking reactions significantly improves the cross-linking degree of waste rubber particles in asphalt, and gives them excellent anti-aging properties, effectively resisting long-term environmental stress, and ensuring performance reliability in practical applications.
[0027] The embodiment of the present invention provides a method for significantly improving the durability and anti-aging properties of asphalt by introducing waste rubber particles modified with oak bark (modified with n-octadecyltrimethoxysilane). The dispersion effect, crosslinking degree, mechanical properties, anti-aging properties and hydrophobicity of the waste rubber particles modified with oak bark in modified asphalt are studied.
[0028] Unless otherwise specified, the experimental methods described in the following examples are all conventional methods; the reagents and materials described are all commercially available unless otherwise specified.
[0029] Example 1
[0030] A method for preparing modified waste rubber particles comprises the following steps:
[0031] S1: preparing a modified mixture: 5 parts of oak bark and 1 part of n-octadecyltrimethoxysilane are mixed in situ to generate a modified oak bark, which is then added into 100 parts of waste rubber particles to generate a modified mixture.
[0032] S2: Premix preparation: A premix containing the modified mixture, 2 parts of a dispersant (stearic acid) and 5 parts of a crosslinking activator (zinc oxide) was prepared using a two-roll mill.
[0033] S3: Preparation of modified waste rubber particles: The obtained premix was sequentially mixed with 1.5 parts of an accelerator (2-mercaptobenzothiazole) and 2 parts of sulfur, and a vulcanization reaction was performed, and then a double-roll mill was used to prepare modified waste rubber particles. The modified waste rubber particles were stored separately in a sealed foil at room temperature.
[0034] Example 2
[0035] A method for preparing modified waste rubber particles comprises the following steps:
[0036] S1: preparing a modified mixture: 10 parts of oak bark and 1 part of n-octadecyltrimethoxysilane are mixed in situ to generate a modified oak bark, which is then added into 100 parts of waste rubber particles to generate a modified mixture.
[0037] S2: Premix preparation: A premix containing the modified mixture, 2 parts of dispersant and 5 parts of crosslinking activator was prepared using a double roll mill.
[0038] S3: Preparation of modified waste rubber particles: The obtained premix was sequentially mixed with 1.5 parts of accelerator and 2 parts of sulfur to carry out vulcanization reaction, and then the modified waste rubber particles were prepared using a double-roll mill. The modified waste rubber particles were stored separately in sealed foil at room temperature.
[0039] Example 3
[0040] A method for preparing modified waste rubber particles comprises the following steps:
[0041] S1: preparing a modified mixture: 15 parts of oak bark and 1 part of n-octadecyltrimethoxysilane are mixed in situ to generate a modified oak bark, which is then added into 100 parts of waste rubber particles to generate a modified mixture.
[0042] S2: Premix preparation: A premix containing the modified mixture, 2 parts of dispersant and 5 parts of crosslinking activator was prepared using a double roll mill.
[0043] S3: Preparation of modified waste rubber particles: The obtained premix was sequentially mixed with 1.5 parts of accelerator and 2 parts of sulfur to carry out vulcanization reaction, and then the modified waste rubber particles were prepared using a double-roll mill. The modified waste rubber particles were stored separately in sealed foil at room temperature.
[0044] Example 4
[0045] A method for preparing modified waste rubber particles comprises the following steps:
[0046] S1: preparing a modified mixture: 20 parts of oak bark and 1 part of n-octadecyltrimethoxysilane are mixed in situ to generate a modified oak bark, which is then added into 100 parts of waste rubber particles to generate a modified mixture.
[0047] S2: Premix preparation: A premix containing the modified mixture, 2 parts of dispersant and 5 parts of crosslinking activator was prepared using a double roll mill.
[0048] S3: Preparation of modified waste rubber particles: The obtained premix was sequentially mixed with 1.5 parts of accelerator and 2 parts of sulfur to carry out vulcanization reaction, and then the modified waste rubber particles were prepared using a double-roll mill. The modified waste rubber particles were stored separately in sealed foil at room temperature.
[0049] Example 5
[0050] A method for preparing modified waste rubber particles comprises the following steps:
[0051] S1: preparing a modified mixture: 25 parts of oak bark and 1 part of n-octadecyltrimethoxysilane are mixed in situ to generate a modified oak bark, which is then added into 100 parts of waste rubber particles to generate a modified mixture.
[0052] S2: Premix preparation: A premix containing the modified mixture, 2 parts of dispersant and 5 parts of crosslinking activator was prepared using a double roll mill.
[0053] S3: Preparation of modified waste rubber particles: The obtained premix was sequentially mixed with 1.5 parts of accelerator and 2 parts of sulfur to carry out vulcanization reaction, and then the modified waste rubber particles were prepared using a double-roll mill. The modified waste rubber particles were stored separately in sealed foil at room temperature.
[0054] Performance Testing
[0055] In order to further prove the elasticity and anti-aging effects of the modified waste rubber particles prepared by the present invention, the following performance tests were conducted, including 100% elongation stress value, tensile strength and elongation at break.
[0056] Modified waste rubber particles with different oak bark contents were prepared by the methods of Examples 1-5, and their tensile strength, elongation at break and stress at 100% elongation were measured. At the same time, they were compared with unmodified waste rubber particles. The results are shown in Table 1.
[0057] Table 1 Test results of elastic properties of modified waste rubber particles
[0058]
[0059]
[0060] The addition of oak bark significantly enhanced the elasticity of rubber particles, and the waste rubber particles containing 10 parts of modified oak bark showed the best elastic properties. Compared with the unmodified rubber particles, the tensile strength increased by 38%, the elongation at break increased by 28%, and the 100% elongation stress value decreased by 16%.
[0061] A single index cannot fully characterize the elastic properties of modified waste rubber particles, and a comprehensive analysis is needed. From the results in Table 1, it can be seen that the modified waste rubber particles with 10 parts of oak bark added have lower 100% elongation stress, higher tensile strength and elongation at break, which generally indicates that they have better elasticity and toughness.
[0062] The elasticity of modified waste rubber particles mainly comes from the flexibility and mobility of their molecular chains, while the degree of cross-linking is a reflection of the number of cross-linking points between molecular chains. Improving the elasticity of rubber particles can increase the freedom of movement of their molecular chains, which helps to form a more uniform and stable cross-linking structure in the modified asphalt, thereby promoting the cross-linking reaction to a certain extent.
[0063] The invention discloses an application of modified waste rubber particles in asphalt and the influence of modified waste rubber particles with different oak bark content on the anti-aging performance of modified asphalt. 15g of the modified waste rubber particles prepared in Examples 1-5 and 100g of No. 70 base asphalt are used to prepare rubber modified asphalt. The preparation method is as follows: heating the No. 70 base asphalt to 180°C, adding the modified waste rubber particles, the shearing time is 4h, and the shearing temperature is 200°C; after the shearing is completed, the asphalt is stirred and developed, 0.08% sulfur stabilizer is added during the stirring and developing, the stirring temperature is 190°C, the stirring time is 2h, and after the stirring and developing, a modified asphalt with enhanced anti-aging performance is obtained.
[0064] At the same time, the waste rubber particles not modified with oak bark and the rubber modified asphalt prepared by the methods of the above Examples 1-5 were used. The high temperature performance and low temperature performance of the modified asphalt were evaluated by softening point value and creep stiffness respectively, and the PAV anti-aging study was conducted on the prepared modified asphalt, and the strength retention rate (AsR index) was used to evaluate its anti-aging performance. The results are shown in Table 2.
[0065] Table 2 Effect of modified rubber particles with different amounts of oak bark added on the properties of modified asphalt
[0066]
[0067] It can be observed from Table 2 that the modification of waste rubber particles will improve the low temperature performance, high temperature performance and anti-aging performance of rubber modified asphalt; the softening point is 77.5℃, the creep stiffness is 115.2MPa, and the PAV strength retention rate before and after aging is 0.598. Among them, the rubber modified asphalt prepared by adding 10 parts of modified waste rubber particles with oak bark has the greatest performance improvement. This may be because the addition of 10 parts of oak bark has the best improvement in the elastic properties of waste rubber particles, thereby improving the degree of crosslinking between it and asphalt; and oak bark contains a large amount of phenolic derivatives, which can be used as an anti-aging agent for materials. Compared with traditional fillers such as silica or carbon black, oak bark reduces environmental pollution and may reduce the carbon footprint of the product. In general, the application of oak bark modified waste rubber particles in modified asphalt not only has environmental advantages, but also significantly improves the crosslinking degree and anti-aging performance of asphalt materials, showing a wide range of application potential.
[0068] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing modified waste rubber particles, characterized in that: The steps include: S1. preparing a modified mixture: mixing oak bark and n-octadecyltrimethoxysilane in situ to generate modified oak bark, and then adding the oak bark into waste rubber particles to generate a modified mixture; S2. Premix preparation: preparing a premix containing a modified mixture, a dispersant and a cross-linking activator by a double-roll mill; S3, preparing modified waste rubber particles: the obtained premix is sequentially mixed with an accelerator and sulfur to carry out a vulcanization reaction, and then a double-roll grinder is used to prepare modified waste rubber particles.
2. The method for preparing modified waste rubber particles according to claim 1, characterized in that: In terms of weight, the ratio of the waste rubber particles, n-octadecyltrimethoxysilane, oak bark, dispersant, cross-linking activator, accelerator and sulfur is 100:1:5 to 25:2:5:1.5:
2.
3. The method for preparing modified waste rubber particles according to claim 1, characterized in that: The density of n-octadecyltrimethoxysilane is 0.88 g / cm 3 ; The dispersant is stearic acid, with a density of 0.94g / cm 3 The cross-linking activator is zinc oxide; the accelerator is 2-mercaptobenzothiazole, with a density of 1.29 g / cm 3 The sulfur density is 1.8 to 2.36 g / cm 3 ;.
4. The method for preparing modified waste rubber particles according to claim 1, characterized in that: In step S2 and step S3, the roller temperature of the double-roll mill is 30-35° C., and the grinding time is 10 minutes.
5. The method for preparing modified waste rubber particles according to claim 1, characterized in that: In step S3, the vulcanization parameters of the vulcanization reaction include a temperature of 160°C, a pressure range of 150-180 bar, and a curing duration of 4 minutes.
6. A modified waste rubber particle prepared according to the method for preparing modified waste rubber particles according to any one of claims 1 to 5, characterized in that: Compared with unmodified waste rubber particles, the modified waste rubber particles have a tensile strength increased by 38%, a breaking elongation increased by 28%, and a 100% elongation stress value decreased by 16%.
7. Use of the modified waste rubber particles prepared by the method for preparing modified waste rubber particles according to any one of claims 1 to 5 or the modified waste rubber particles according to claim 6 in asphalt.
8. The use of modified waste rubber particles in asphalt according to claim 7, characterized in that: Heat No. 70 base asphalt to 180°C, add modified waste rubber particles, the shear time is 4 hours, and the shear temperature is 200°C; after the shearing is completed, the asphalt is stirred and developed, and 0.08% sulfur stabilizer is added during the stirring and development period. The stirring temperature is 190°C and the stirring time is 2 hours. After stirring and development, modified asphalt with enhanced anti-aging properties is obtained.
9. The use of modified waste rubber particles in asphalt according to claim 8, characterized in that: The added amount of the modified waste rubber particles is 15-25% of the mass of the asphalt.
10. The use of modified waste rubber particles in asphalt according to claim 7, characterized in that: The softening point of the modified asphalt is 77.5° C., the creep stiffness is 115.2 MPa, and the strength retention rate before and after PAV aging is 0.598.